Signaling through the Primary Cilium - Wheway, Gabrielle; Nazlamova, Liliya; Hancock, John T. (Frontiers in Cell and Developmental Biology, 2018)
The presence of single, non-motile ‘primary’ cilia on the surface of epithelial cells has been well described since the 1960s. However, for decades these organelles were believed to be vestigial, with no remaining function, having lost their motility. It wasn’t until 2003, with the discovery that proteins responsible for transport along the primary cilium are essential for hedgehog signaling in mice, that the fundamental importance of primary cilia in signal transduction was realised. Little more than a decade later, it is now clear that the vast majority of signaling pathways in vertebrates function through the primary cilium. This has led to the adoption of the term ‘the cells’s antenna’ as a description for the primary cilium. Primary cilia are particularly important during development, playing fundamental roles in embryonic patterning and organogenesis, with a suite of inherited developmental disorders known as the ‘ciliopathies’ resulting from mutations in genes encoding cilia proteins. This review summarises our current understanding of the role of these fascinating organelles in a wide range of signaling pathways.